2019
DOI: 10.3389/fgene.2019.00196
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Suggests the Roles of Long Intergenic Non-coding RNAs in the Growth Performance of Weaned Piglets

Abstract: Long intergenic non-coding RNAs (lincRNAs) have been considered to play a key regulatory role in various biological processes. An increasing number of studies have utilized transcriptome analysis to obtain lincRNAs with functions related to cancer, but lincRNAs affecting growth rates in weaned piglets are rarely described. Although lincRNAs have been systematically identified in various mouse tissues and cell lines, studies of lincRNA in pigs remain rare. Therefore, identifying and characterizing novel lincRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 59 publications
2
18
0
Order By: Relevance
“…2 D). Which were highly consistent with previous reports 22 , 23 .
Figure 2 Characterization of lincRNAs compared with protein-coding genes; (A) Comparison of transcript length; (B) Comparison of exon length; (C) Comparison of numbers of exon; (D) Comparison of expression level.
…”
Section: Introductionsupporting
confidence: 94%
“…2 D). Which were highly consistent with previous reports 22 , 23 .
Figure 2 Characterization of lincRNAs compared with protein-coding genes; (A) Comparison of transcript length; (B) Comparison of exon length; (C) Comparison of numbers of exon; (D) Comparison of expression level.
…”
Section: Introductionsupporting
confidence: 94%
“…They also reported the potential lncRNA ( Yan et al, 2018a ) and circRNA ( Yan et al, 2018b ) functions in the spleen of diarrheic piglets caused by CPID. Liu et al (2018) and Chen et al (2019) revealed the potential role of lncRNA or circRNA in muscle and fat development in piglets. lncRNA was also found to be associated with oxidative stress in piglet ( Wang J. et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…And the assembled transcriptome was then filtered to obtain the putative lincRNAs. Our pipeline for lincRNA identification as shown in Figure S1A was based on the way described in our previous study [41,42].…”
Section: Identification and Function Analysis Of Lincrnasmentioning
confidence: 99%